Pengaruh Kompensasi dan Kompetensi terhadap Produktivitas Kerja Karyawan - Hendi, Aji Muhamad; Huda, Badriyatul (Ma'soem University, 2025)
Based on the observation results, this research is motivated by fluctuations in the number of employees at Bank Syariah Indonesia East Bandung Branch Office which is influenced by the compensation and competencies provided by the company. This study aims to determine the effect of compensation and competence on employee productivity, both partially and simultaneously, at Bank Syariah Indonesia's East Bandung Branch Office. Type This associative quantitative study involved employees of Bank Syariah Indonesia at the Cinunuk and Rancaekek Sub-Branch Offices. Primary data was collected through observation, interviews, literature study, and questionnaires. Using a saturated sampling technique, all 31 employees were used as respondents. This study employed multiple correlation analysis, multiple regression analysis, and determination coefficient analysis, as well as t-tests and F-tests. The research results show that there is a significant effect of compensation on employee work productivity, with the t-test result showing t-count > t-table (3.881 > 70113) and a coefficient of determination of 33.4%. There is a significant effect of competence on employee work productivity, with the t-test result showing t-count > t-table (9.679 > 1.70113) and a coefficient of determination of 76.4%. Furthermore, simultaneously, there is a significant effect of both compensation and competence on employee work productivity, with the F-test result showing F-count > F-table (49.311 > 3.37) and a coefficient of determination of 77.9%.